THE RELATIONSHIP BETWEEN DELAY HANDLING OF PASSENGER AND ON TIME PERFORMANCE OF ETIHAD AIRWAYS AT SOEKARNO HATTA INTERNATIONAL AIRPORT - Husni Hasan; Ananda Anggia; Alit Sodikin (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The on time performance of Etihad Airways is still below target. Therefore, in order to achieve the target, Etihad Airways decided punctuality as one of the fundamental missions of the company. The issue of timeliness of departure  that Etihad airways have is because of many factors, one of them is a delay in the handling passengers. Delays in handling passengers also included in the factors causing delays in the departure of Etihad Airways aircrafts. This research aims to analyze the delay in handling of passengers related to on time departure performance Etihad Airways in Soekarno-Hatta Jakarta, in analyzing the the research data, authors used descriptive research method by doing observations, survey and questionnaire.  The results show Etihad Airways should improve the staff in making a good on time performance for their departure.  About 78.76% of the handling of passengers on Etihad Airways Jakarta has been quite good.  In addition, the on time performance on Etihad Airways in Jakarta is also quite good.  However, no respondents chose the hesitation option in responding the questionnaire.  40.99% of the respondent did not agree.  It  means that although the on time performance of Etihad Airways in Jakarta is quite good but  Etihad Airways still experience constraints in the timelines of its departure